2021
DOI: 10.48550/arxiv.2109.08955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Manifold-preserved GANs

Abstract: Generative Adversarial Networks (GANs) have been widely adopted in various fields. However, existing GANs generally are not able to preserve the manifold of data space, mainly due to the simple representation of discriminator for the real/generated data. To address such open challenges, this paper proposes Manifold-preserved GANs (MaF-GANs), which generalize Wasserstein GANs into high-dimensional form. Specifically, to improve the representation of data, the discriminator in MaF-GANs is designed to map data in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Benefiting from DLLE and DIsoMap, our method, namely MaEM-GAN, maximizes the entropy in the well-learned embedding space to combat the mode collapse in GANs. Experimental results show that the proposed MaEM-GAN outperforms the recent advanced GAN method MaF-GAN (Liu et al 2021) on CelebA (9.13 vs. 12.43 in FID) and surpasses the recent state-of-the-art EBM (Geng et al 2021) • We propose a novel training pipeline to address the mode collapse issue in GANs, which effectively alleviates mode collapse without sacrificing the image quality of generated images.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Benefiting from DLLE and DIsoMap, our method, namely MaEM-GAN, maximizes the entropy in the well-learned embedding space to combat the mode collapse in GANs. Experimental results show that the proposed MaEM-GAN outperforms the recent advanced GAN method MaF-GAN (Liu et al 2021) on CelebA (9.13 vs. 12.43 in FID) and surpasses the recent state-of-the-art EBM (Geng et al 2021) • We propose a novel training pipeline to address the mode collapse issue in GANs, which effectively alleviates mode collapse without sacrificing the image quality of generated images.…”
Section: Introductionmentioning
confidence: 91%
“…The empirical and theoretical study pointed out that the learning objective of GANs might neglect an intractable entropy term for maximum likelihood, which plays a key point in the mode collapse and can be effectively tackled by high-dimensional GANs. Manifold-preserved GAN (Liu et al 2021) is the most similar work to ours; however, it neglects the entropy term.…”
Section: Related Workmentioning
confidence: 96%
See 2 more Smart Citations
“…The recent advances in convolutional neural networks (CNNs) have yielded significant improvements to various computer vision tasks, such as image classification [14,31,39] and image generation [10,19,30]. However, recent studies [16,38] revealed that CNN based models are vulnerable to the adversarial attacks and out-of-distribution samples, which seriously limits their applications in security-critical scenarios, e.g., self-driving [40], medical imaging [33] and biometrics [28,29].…”
Section: Introductionmentioning
confidence: 99%